Analisis Semiotika Ferdinand De Saussare pada Album “Dalam Dinamika” karya Perunggu - Elisa Elisa; Aditya Ansor Alsunah; Cecep Dudung Julianto; Lina Siti Nurwahidah (eScience Humanity Journal, 2026)
This study aims to analyze the signifiers and signified in the song lyrics of the album dalam Dinamika by Perunggu and to interpret the meanings that emerge from the interaction between the two. This study employed a descriptive qualitative method using the semiotic approach developed by Ferdinand de Saussure. The data analyzed consisted of song lyrics from the album Dalam Dinamika, including “Tapi”, “Pikiran yang Matang”, “Aku Ada Untukmu”, and “Amalan Baik”. Data collection was conducted though literature study and documentation techniques, while the data were analyzed using content analysis. The finding of this study indicate that the meaning contained in the album dalam Dinamika are constructed through the relationship between signifiers and signifieds, reflecting the life experiences  of young g people. The songs “Tapi” and “Amalan Baik” represent struggles and the search for life direction, “Pikiran yang Matang” portrays emotional closeness and nostalgia. Overall, the songs in this album reflect the dynamics of life through the semiotic perspective of Ferdinand de Saussure.